Hepatocurative Effect of Methanol Extract of Newbouldia laevis Leaves in Alloxan-Induced Liver Damage in Albino Rats - Umaru, Isaac John; Rebecca, Tsokwa Punarimam; Tansaba, Akafa Andes; Nanmar, Chakfa; Umaru, Kerenhappuch Isaac; Ugoeze, Egeonu Stephen; Danjuma, Tyem Lawal (Darul Yasin Al Sys, 2024)
The aim of the study is to evaluate the effect (Hepatocurative and antibacterial potential) of Newboulda laevis leaves in alloxan-induced liver damage in Wister Albino Rats. The leaves of Newbouldia laevis was bought from a local market in Wukari, Taraba State. The leaves of Newbouldia laevis was chop and then pulverized into fine powder. The methanol crude extracts andthirty-two albino Wistar rats weighing 90-220 g was used for this research. Liver toxicity was induced in male rats by an intraperitoneal single dose of 150 mg/kg body weight. samples were subjected to biochemical estimation of liver function. The result showed a significant (p≤0.05) increase in serum AST level for group II (60.6 ± 1.12) which was administered high dose of Alloxan and serves as the negative control group, when compared to the normal control group I (35.09 ± 2.07) which only received feed and water. From the result described in table 4.0 above, it showed a significant (p≤0.05) increase in ALT level for group II (58.11 ± 0.42) negative control when compared with group I (20.00 ± 0.41) normal control. Group III (29.98 ± 0.12) which received standard drug showed a significant decrease in ALT which is a sign that there is some level of repair on the liver cells. Group IV (36.22 ± 0.s70), group V (30.00 ± 0.27) and group VI (29.99 ± 0.12) which received 100, 200 and 400 mg/kg body weight of Newbouldia laevis leaves extract respectively when compared with the negative control group II, showed a significant decrease in ALT level. There was a significant (p≤0.05) increase in ALP level for group II (255.80 ± 1.12) which received Alloxan when compared with the normal control group I (80.21 ± 0.44) providing evidence to support the increase in ALT and AST level in group II, suggestive of liver injury. The treatment groups III, VI, V and VI showed significant (p<0.05) difference, when compared to the negative control group. No significant (p<0.05) difference between group V and VII. It was deduced that the total protein for group II (10.95 ± 0.37) significantly (p<0.05) decreased when compared to the normal control group I (14.13 ± 0.55). This is because low levels of total protein in the blood can occur because of impaired function of the liver. Administration of Newbouldia laevis leaves extract significantly (p<0.05) elevated total protein levels for group IV (10.99 ± 0.41), V (12.76 ± 0.41) and VI (12.98 ± 0.58). Albumin being the most abundant protein in the blood, equally followed same pattern as total protein, with Albumin level of (10.83 ± 0.10), (6.13 ± 0.05), (9.82 ± 0.18) (6.75 ± 0.13), (7.99 ± 0.10) and (9.60 ± 0.13) for group I, II, III, IV, V and V respectively. Thus, emphasizing the potential of the extract as a source agent for medication for ailment and diseases.